PENGARUH MODEL PEMBELAJARAN AUDITORY, INTELLECTUALLY, AND REPETITION (AIR) BERBANTUAN APLIKASI KAHOOT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Yani, Juliandri; Minta Ito Simamora; Khoiruddin Matondang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Auditory, Intellectually, and Repetition (AIR) learning model assisted by the Kahoot application on students’ mathematical problem-solving ability and examine its effectiveness in the learning process. This experimental study used a pretest–posttest control group design. The population consisted of 55 tenth-grade students of SMKS Al Washliyah Pasar Senen 2 Medan. Probability sampling selected two classes: experimental (30 students) and control (25 students). Research instruments included problem-solving tests and learning effectiveness questionnaires. Results showed that the experimental class achieved a higher posttest mean score (46.33) than the control class (36.59). A t-test indicated a significant difference (Sig. 0.000 < 0.05). Questionnaire results showed a “very good” category with 87.8% and 85.28% for experimental and control classes, respectively. This proves that applying the AIR model assisted by Kahoot effectively improves students’ mathematical problem-solving ability. This study aims to determine the effect of the Auditory, Intellectually, and Repetition (AIR) learning model assisted by the Kahoot application on students’ mathematical problem-solving ability and examine its effectiveness in the learning process. This experimental study used a pretest–posttest control group design. The population consisted of 55 tenth-grade students of SMKS Al Washliyah Pasar Senen 2 Medan. Probability sampling selected two classes: experimental (30 students) and control (25 students). Research instruments included problem-solving tests and learning effectiveness questionnaires. Results showed that the experimental class achieved a higher posttest mean score (46.33) than the control class (36.59). A t-test indicated a significant difference (Sig. 0.000 < 0.05). Questionnaire results showed a “very good” category with 87.8% and 85.28% for experimental and control classes, respectively. This proves that applying the AIR model assisted by Kahoot effectively improves students’ mathematical problem-solving ability.